Evaluation of Split Suckling Strategies on Pre- and Post-Weaning Piglet Growth and Mortality - Mikayla S. Spinler; Samantha A. Swanson; Elizabeth Due; Maya Lashley; Ashley R. Hartman; Jordan T. Gebhardt; Katelyn N. Gaffield; Joel M. DeRouchey; Mike D. Tokach; Robert D. Goodband; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 1,513 sows, approximately 505 sows per treatment, and their litters were used in a 20-d lactation study to determine the effects of split-suckling strategies on litter growth, pre-weaning mortality, and post-weaning performance. Sows were blocked by parity, and sows and their litters were allotted to one of three treatments consisting of a control treatment with no split-suckling, or one of two treatments using different split-suckle protocols. For split-suckle treatment 1, litters were split-suckled based on birth order, with the first eight pigs born marked at birth, and upon the completion of farrowing, the eight marked pigs were removed from the sow for 45 min. After 45 min, the eight marked pigs were placed back on the sow, and the unmarked pigs born later in the birth order were removed from the sow for 45 min, and then all pigs were returned to the sow. For split-suckle treatment 2, after farrowing was completed, the eight heaviest pigs in the litter were removed from the sow for 1.5 h and then returned to the sow, completing the split-suckle treatment. Litters on split-suckle strategies 1 and 2 were split-suckled within 18 h of birth. Cross-fostering occurred within treatment 24 h after the completion of farrowing and after the split-suckling treatment was applied. Fallback pigs were identified from d 2 to 12 after birth, pulled, and placed on a nurse sow. There were no differences (P > 0.10) in litter size at d 1 or weaning. Piglet weights on d 1 and weaning were not different (P > 0.10) among treatments. No differences (P > 0.10) in pre-weaning mortality from d 1 to d 2, d 2 to weaning, or overall were observed. There was no difference (P > 0.10) in the percentage of fallback pigs fostered to a nurse sow. Pre-weaning mortality was analyzed by body weight category at birth within treatment, light (≤ 2.6 lb), medium (2.7 < × ≤ 3.2 lb), and heavy (≥ 3.3 lb) pigs; with no differences (P > 0.10) in pre-weaning mortality from d 1 to weaning observed. A subset of pigs was followed into the nursery and finisher to track post-weaning growth performance and mortality, with no differences (P > 0.10) in ADG, ADFI, F/G, or mortality observed in the nursery or finisher. Overall, the split-suckle strategies used in this study did not affect pig growth performance or mortality pre- or post-weaning compared to not split-suckling.
Keywords: growth performance; pre-wean mortality; split-suckle